The peculiar journey: race, racism, and imprisonment in American history - Crutchfield, Robert D. (Crime and justice, 2022)
“The problem of the twentieth century is the problem of the color-line” wrote W. E. B. Du Bois in The Souls of Black Folk. That remains true in twenty-first-century America, especially in criminal justice systems generally and particularly in prisons. Racial disparities in sentencing and in imprisonment have declined slightly from historic peaks in the 1980s and 1990s but remain stubbornly high. Differential criminal justice system treatment of Blacks and Whites has changed form since the Civil War but endured as convict labor, prison farms, imprisonment rate disparities, contemporary tough-on-crime laws, and police practices that target members of minority groups, places they frequent, and behaviors for which they are disproportionately often arrested. In earlier times, differential treatment was often openly invidious. In more recent times it is nominally color-blind but produces similarly skewed results. We need to understand why and how differential treatment of Black people has persisted through a century and a half of fundamental changes in criminal justice system policies and practices and how this has happened within the context of shifting notions of what race is and what constitutes racism.